High-speed X-ray visualization of dynamic crack initiation and propagation in bone. (May 2019) - Zhai, Xuedong; Guo, Zherui; Gao, Jinling; Kedir, Nesredin; Nie, Yizhou; Claus, Ben; Sun, Tao; Xiao, Xianghui; Fezzaa, Kamel; Chen, Weinong W.
Graphical abstract: Abstract: The initiation and propagation of physiological cracks in porcine cortical and cancellous bone under high rate loading were visualized using high-speed synchrotron X-ray phase-contrast imaging (PCI) to characterize their fracture behaviors under dynamic loading conditions. A modified Kolsky compression bar was used to apply dynamic three-point flexural loadings on notched specimens and images of the fracture processes were recorded using a synchronized high-speed synchrotron X-ray imaging set-up. Three-dimensional synchrotron X-ray tomography was conducted to examine the initial microstructure of the bone before high-rate experiments. The experimental results showed that the locations of fracture initiations were not significantly different between the two types of bone. However, the crack velocities in cortical bone were higher than in cancellous bone. Crack deflections at osteonal cement lines, a prime toughening mechanism in bone at low rates, were observed in the cortical bone under dynamic loading in this study. Fracture toughening mechanisms, such as uncracked ligament bridging and bridging in crack wake were also observed for the two types of bone. The results also revealed that the fracture toughness of cortical bone was higher than cancellous bone. The crack was deflected to some extent at osteon cement line in cortical bone instead of comparatively penetrating straight through the microstructures in cancellous bone. Statement of Significance: Fracture toughness is with great importance to study for crack risk prediction in bone. For those cracks in bone, most of them are associated with impact events, such as sport accidents. Consequently, we visualized, in real-time, the entire processes of dynamic fractures in notched cortical bone and cancellous bone specimens using synchrotron X-ray phase contrast imaging. The onset location of crack initiation was found independent on the bone type. We also found that, although the extent was diminished, crack deflections at osteon cement lines, a major toughening mechanism in transversely orientated cortical bone at quasi-static rate, were still played a role in resisting cracking in dynamically loaded specimen. These finding help researchers to understand the dynamic fracture behaviors in bone.